Extraction and modification of hemicellulose from wheat bran to produce entrapment materials for the controlled release of chemicals and bioactive substances - Matavire, Thokozani Olga (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.